Effects of prescribed fire and mechanical thinning on oak regeneration and white-tailed deer activity in a Kansas woodland - Wurtz, Joshua Cody (Kansas State University, 2024)
Transformation from desirable to undesirable tree species is an issue concerning woodland managers across the United States. Forests, woodlands, and tree cover occupy 5.2 million acres in Kansas, representing 10 percent of the total land area. Oak (Quercus spp.) woodlands are common across eastern Kansas and are transitioning from shade intolerant to shade tolerant species, such as hackberry (Celtis occidentalis), American elm (Ulmus americana), Eastern redcedar (Juniperus virginiana), and redbud (Cercis canadensis). A 10-year repeated measures study was conducted from 2014 to 2023 on a 90-acre tract dominated by chinkapin oak near Manhattan, Kansas to determine the effects of repeated prescribed fire and mechanical thinning in an oak woodland on woody vegetation. In addition, White-tailed deer activity was monitored from July 2022 to January 2024 to understand deer activity within forestry treatments. Our results indicated Burn Only and Thin Only had the greatest increase in oak seedlings during the duration of the study period. Competitor species were most abundant in the Burn and Thin areas at the conclusion of our study. Deer activity was highest in Burn Only and Control areas during our study period, but activity shifted to Burn Only and Burn and Thin areas during the Fawn Rearing and Antler Growing season for does, indicating does are using areas during this season that were managed with prescribed fire. Undesired, shade tolerant species will continue to dominate the seedling stage without proper management, and periodic fires can be effective for improving deer habitat in hardwood systems.
Keywords: Oak; Wildlife; Prescribed fire; Deer; Thinning; Forest